2017
DOI: 10.1088/2058-6272/aa6a51
|View full text |Cite
|
Sign up to set email alerts
|

On peak current in atmospheric pulse-modulated microwave discharges by the PIC-MCC model

Abstract: Pulse modulation provides a new way to tailor the electron density, electron energy and gas temperature in atmospheric radio-frequency (rf) discharges. In this paper, by increasing the rf frequency to several hundreds of MHz, or even much higher to the range of GHz, a very strong peak current in the first period (PCFP) with much larger electron energy can be formed during the power-on phase, which is not observed in the common pulse modulation discharges at a rf frequency of 13.56 MHz. The PIC-MCC model is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…It is indicated that the pulsed discharge effectively enhances the ignition intensity of RF discharge, especially during the first few cycles of the RF discharge, which also has been demonstrated by the experimental investigations [38], [39]. In addition, high-energy electrons generated in the LDCs are expected to have implications for many applications [42], [48], and the underpinning physics should be further clarified by computational data.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…It is indicated that the pulsed discharge effectively enhances the ignition intensity of RF discharge, especially during the first few cycles of the RF discharge, which also has been demonstrated by the experimental investigations [38], [39]. In addition, high-energy electrons generated in the LDCs are expected to have implications for many applications [42], [48], and the underpinning physics should be further clarified by computational data.…”
Section: Resultsmentioning
confidence: 68%
“…The peak values of LDCs are 16.6 and 16.3 A/cm 2 , respectively, which are nearly 13% stronger than those in the stable state of 14.6 A/cm 2 . Compared to the counterpart without dielectric barriers that only one positive LDC can be generated in [42], [49], and [44], double LDCs indicate that the high-energy electrons could be produced two times during the positive and negative half-cycles, which makes this kind of discharge have great potential and advantages in numerous applications. But the mechanisms on the production of LDCs have not yet been fully investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…然而, 随着输入 功率的增加, 放电比较容易转化成为体积较小、发光 明亮的热等离子体, 电流密度增加而总电流减小, 这 就进入了所谓的γ模式 [18,19] . 为了有效地抑制这种模 式转换, 人们已经发展了一些行之有效的方法, 比如 降低放电间隙、提高放电频率, 对放电进行脉冲调制 等 [18,20,24,25] .…”
Section: 张远涛等 中国科学: 物理学 力学 天文学 2018年 第48卷 第2期unclassified